Pengaruh Inflasi, Cadangan Devisa, Dan Produk Domestik Bruto Terhadap Impor Barang Modal - Mardianto, Agung; Kusumajaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 9, September 2014 (pp. 395-430), 2014)
Indonesia is rich in natural resources but have not been able to meet its own needs, for the import of capital goods was undertaken. With the import of capital goods are expected to produce the goods that are not always dependent on other countries. Imports of capital goods can be affected by inflation, foreign exchange reserves, and the gross domestic product. The purpose of this study was to examine the effect of the inflation rate, foreign exchange reserves of the Indonesian capital goods imports in 1994-2011. This study uses secondary data sourced from the Central Bureau of Statistics and Bank Indonesia, which were then analyzed using multiple linear regression analysis. The results based on multiple linear regression analysis showed that inflation, foreign exchange reserves, and the gross domestic product simultaneously significant effect on the import of capital goods in Indonesia in 1994-2011. However partially, the variable gross domestic product are significant effect.
Keywords: gross domestic product; consumption; investment; inflation